Factors, markers, diagnostic methods, and prediction of pregnancy loss - P. A. Koshulko; A. M. Kirsanova-Martynova; V. A. Buchnev; E. V. Ignatova; S. S. Kupriyanov; E. S. Melnikov; P. A. Solodov; A. M. Dorogova; G. D. Bagirova; A. V. Zubkov; A. D. Kolyvanova; E. A. Zubareva; et al. (Опухоли женской репродуктивной системы, 2021)
Aim. To evaluate the risk factors associated with pregnancy loss in the studied cohort; to establish the clinical relevance of leukocyte-derived proteolytic enzymes as biomarkers of pregnancy loss; to develop a diagnostic and prognostic approach for early detection of pregnancy loss.Materials and methods. The study included 152 participants aged 18 to 40 years: 35 conditionally healthy pregnant women and 117 patients diagnosed with threatened miscarriage at 5–6 weeks of gestation. These patients, based on the activity levels and quantity of leukocyte-derived proteolytic enzymes and/or pregnancy outcomes, were divided into three groups: 35 patients with a missed miscarriage, 35 patients with a complete spontaneous abortion, and 35 patients with an incomplete spontaneous abortion.The diagnosis of threatened miscarriage was established based on clinical presentation (complaints of lower abdominal cramping and/or vaginal bleeding), as well as ultrasound findings (presence of a gestational sac in the uterine cavity). The diagnosis of complete spontaneous abortion in the main group was based on the absence of a gestational sac in the uterine cavity as confirmed by ultrasound and/or the identification of chorionic tissue on histological examination. The diagnosis of incomplete spontaneous abortion was based on the presence of retained products of conception in the uterine cavity and confirmation of chorionic tissue in histological analysis. The diagnosis of a missed miscarriage was based on deformation of the gestational sac and/or absence of embryonic cardiac activity on ultrasound. To assess cathepsin activity, biochemical assay kits were used, and the resulting data were analyzed using spectrofluorimetric methods.Results. The new method for early diagnosis of pregnancy loss possesses high sensitivity and specificity.Conclusion. The study confirmed that cathepsins are markers of miscarriage, and a method for early diagnosis and prediction of this pregnancy pathology before its clinical manifestations and pregnancy outcome was developed.